Outcomes after Community Discharge from Skilled Nursing Facilities: The Role of Medicaid Home and Community‐Based Services. (15th September 2021) - Wang, Sijiu; Temkin‐Greener, Helena; Simning, Adam; Konetzka, R. Tamara; Cai, Shubing
Abstract : Research Objective: Most older adults receiving post‐acute care in skilled nursing facilities (SNFs) return home, but remaining in the community after SNF discharge is challenging, especially for Medicare‐Medicaid dually enrolled individuals (duals). The Medicaid Home‐ and Community‐Based Services (HCBS) may facilitate smoother transitions and support community living after duals return home from SNFs. This study examined the association between the generosity of Medicaid HCBS and health outcomes and care utilization of duals after SNF‐to‐community discharge. Study Design: We merged national Medicare enrollment and claims data, Medicaid Analytic eXtract (MAX), Minimum Data Set, and facility/county‐level publicly available data for CY 2010‐2013. Eligible dual beneficiaries and their SNF post‐acute episodes and SNF‐to‐community discharges were identified. The main outcome variable was whether an individual remained in the community after SNF discharge without "adverse" events (i.e., nursing home [NH] or SNF admission, hospitalization, and death) during two follow‐up periods (i.e., 30 days and 180 days post‐discharge). We further examined each of these events separately as secondary outcomes. The key independent variables included HCBS generosity, measured as breadth (i.e., proportion of duals using HCBS services) and intensity (i.e., average monthly HCBS spending per user). Linear probability models with SNF fixed effects and robust standard errors were estimated, accounting for individual demographics and health status at SNF discharge. Population Studied: The study cohort was duals who were newly admitted to SNFs for post‐acute care and were discharged to the community within 100 days (n=121, 184). Principal Findings: Overall, 79% and 50% of the identified duals remained in the community alive without NH/SNF admissions or hospitalizations for 30 and 180 days after SNF discharge, respectively. After accounting for covariates and SNF fixed‐effects, we found that a 10 percentage‐point increase in HCBS breadth led to a 0.7 percentage‐point increase (p<0.01) and a 0.8 percentage‐point increase (p=0.037) in the likelihood of remaining in the community for 30 and 180 days. A 100 increase in HCBS intensity led to a 0.2 percentage‐point increase (p<0.01) in the likelihood of remaining in the community for 30 days. Increases in both HCBS breadth and intensity were associated with reduced risks of NH/SNF admission within 30 and 180 days, and greater intensity was related to reduced risk of hospitalizations within 30 days after SNF discharge. We did not detect statistically significant associations between HCBS generosity and death in both post‐discharge periods. Conclusions: We found that greater HCBS breadth was associated with higher likelihood of remaining in the community for both the 30‐ and 180‐day periods after SNF discharge, while the effect of HCBS intensity on remaining in the community was detected only in the 30‐day period after discharge. Implications for Policy or Practice: While both HCBS breadth and intensity have a modest effect on facilitating community living after SNF discharge, the role of breadth and intensity may be different. Refining and tailoring the use of HCBS to better meet the needs of patients after discharge from post‐acute care has potential to enhance the ability of duals to remain in the community. Primary Funding Source: National Institutes of Health